Mind over muscle: A conceptul piece comparing the simtween the philosophy of judo and self-directed learning - Michael Duncan Overton (Adult Education Research Conference, 2014)
This is an exploratory examination of the similarities of the core principles of Judo and Self-Directed Learning (SDL). Both Judo and SDL can be considered ways of life that the student is committed to. By comparing the similarities between each educational theory this paper seeks to add another beam of support to the bridge between Eastern and Western ideologies.